2016
DOI: 10.3390/ijms17091484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyrotropin on Osteopontin, Integrin αvβ3, and VCAM-1 in the Endothelium via Activation of Akt

Abstract: Numerous epidemiological studies have shown that subclinical hypothyroidism (SCH) can impair endothelial function and cause dyslipidemia. Studies have evaluated the effects of thyroid stimulating hormone (TSH) on endothelial cells, but the mechanism underlying the proatherosclerotic effect of increased TSH levels remains unclear. In the present study, SCH rat models were established in thyroidectomized Wistar rats that were given l-T4 daily. The results showed that in vivo, the expression of osteopontin (OPN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Increased TSH and normal serum TT 4 levels in the SCH group as compared to the NC group 4 w after L-T 4 injection to 14 w indicated the successful establishment of the SCH rat model. Consecutively, increased TSH and decreased TT 4 levels were also observed in the CH group ( 22 ).…”
Section: Resultsmentioning
confidence: 83%
“…Increased TSH and normal serum TT 4 levels in the SCH group as compared to the NC group 4 w after L-T 4 injection to 14 w indicated the successful establishment of the SCH rat model. Consecutively, increased TSH and decreased TT 4 levels were also observed in the CH group ( 22 ).…”
Section: Resultsmentioning
confidence: 83%
“…51 In another study using TSH as a stimulator, the enhancement of VCAM-1 was accompanied by ERK1/2 activation in HUVECs. 52 It was also observed that TNFa induced activation of JNK and p38 promoted endothelial activation resulting in enhanced VCAM-1 expression in an in vitro experiment using HUVECs, while inhibition of p38, JNK or NF-kB blocked the expression of VCAM-1. 53 In another commonly used endothelial cell type, human aortic endothelial cells (HAECs), a similar phenomenon was observed.…”
Section: Discussionmentioning
confidence: 92%
“…This result may be explained by epidermal growth factor receptor (EGFR) and TGFβRI/II pathway-dependent activation of ERK1/2, which induced phosphorylation in a biphasic and time-dependent manner following the stimulation of fibroblasts with TGF-β1 [ 46 ]. Alternatively, the delayed ERK1/2 signaling may have been in response to FN type III, OPN or VCAM1 binding to their integrin receptor sites at distal locations [ 47 ]. However, phosphorylation of FAK protein showed significantly less activation, indicating the prolonged inhibition of the integrin/FAK signaling pathway could be achieved by the AF38Pep blocking polypeptide.…”
Section: Resultsmentioning
confidence: 99%
“…Use of the IST-9 antibody resulted in similar signaling inhibition of FAK at 12 h post-treatment ( Figure S1 ). However, IST-9 prevention of ERK1/2 phosphorylation at the 12 h timepoint suggested the blockade of additional non-EDA-FN-specific ITGA4 activation may have been implicated [ 47 ]. Matrix metalloproteinase (MMP) gelatinase release and activity has been associated with fibronectin-dependent activation of integrin α 4 β 1 and other β 1 -containing integrins [ 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation